EMPOWERING WOMEN SELF HELP GROUPS THROUGH MICROFINANCE DURING COVID-19: A CASE STUDY OF WOMEN SHG - Sharma, Richa; Mishra, Saurabh; Rai, Shashikant (Indian Journal of Finance and Banking, 2021)
The paper describes the mitigating effect of self-help groups in India during and post covid-19 situation. The study examines the potential opportunities and challenges concerning the contextual differences across and within the countries. Self-help group has been important in empowering its members by providing opportunities for livelihood support and income generator during the covid-19 situation. The self-help group played a very important role during the covid-19 situation as half of the SHG was involved in community awareness and infection prevention activities in their community. The study identifies a potential mechanism through which women's groups may be affected by covid-19 situations.JEL Classification Codes: G21, I3.